2013
DOI: 10.1093/gerona/glt015
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis Reveals Novel Features of the Muscle Aging Process in Men and Women

Abstract: To develop a global view of muscle transcriptional differences between older men and women and sex-specific aging, we obtained muscle biopsies from the biceps brachii of young and older men and women and profiled the whole-genome gene expression using microarray. A logistic regression-based method in combination with an intensity-based Bayesian moderated t test was used to identify significant sex- and aging-related gene functional groups. Our analysis revealed extensive sex differences in the muscle transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 41 publications
1
64
1
Order By: Relevance
“…The main goal of this study is to extend the work reported by Liu et al [2] by identifying important genes with good generalization ability. So in this work we prefer to applied work reported by Liu et al [2], propose a method and make a comparison with them in order to show the effectiveness of our approach using two datasets which will be explained in proposed method and material section.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The main goal of this study is to extend the work reported by Liu et al [2] by identifying important genes with good generalization ability. So in this work we prefer to applied work reported by Liu et al [2], propose a method and make a comparison with them in order to show the effectiveness of our approach using two datasets which will be explained in proposed method and material section.…”
Section: Introductionmentioning
confidence: 94%
“…Sexual dimorphism of skeletal muscle can occur due to age [1] and many of these age-related changes in skeletal muscle appear to be influenced by gender [2], [17], [18]. For example, the muscle mass of men is larger than that of women, especially for type II fibers, while the type I muscle fibers proportion of oxidative is higher in women [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations